"Manning Up" to be a Good Father: Hybrid Fatherhood, Masculinity, and U.S. Responsible Fatherhood Policy. Issue 4 (August 2018) - Randles, Jennifer
Drawing on theories of masculinities, I analyze how a U.S. government funded "responsible fatherhood" program utilized a political discourse of hybrid masculinity to shape disadvantaged men's ideas of successful fathering. Using data from three sources that uniquely traces how this discourse traveled from policy to program implementation—including analysis of the curriculum, in-depth interviews with 10 staff, and in-depth interviews and focus groups with 64 participating fathers—I theorize hybrid fatherhood. As a discourse of paternal involvement that incorporates stereotypically feminine styles such as emotional expressiveness, hybrid fatherhood discursively reconfigures patriarchy by drawing distinctions between mothering and fathering and dominant and subordinate forms of masculinity as they relate to men's parenting. I analyze how the promotion of hybrid fatherhood for poor men of color legitimates and sustains gender, race, and class inequalities through U.S. welfare policy.